Hubungan Berat Badan Lahir, Lingkungan Dan Status Imunisasi Dengan Kategori Tingkat ISPA Pada Balita Di Wilayah Kerja Puskesmas Sukaraja Nuban Kabupaten Lampung Timur - Rahmawati, Mega; Purnomo, Heri; HS, Sielvia (Akademi Kebidanan Bunga Husada Samarinda, 2019)
ARI or Acute Respiratory Infections is a group of diseases who attack the respiratory duct. ARI file of cases in public health center Sukaraja Nuban in 2018 as many as 83.554 cases. The purpose of this research is to know the correlation between baby weight, immunization status and the environment with the ARI level category of toddler in working area Public Health Center Sukaraja Nuban East Lampung. The purpose of this research are Knowing the relationship between Birth Weight, Environment and Immunization Status with the incidence of ARI in Toddlers in Sukaraja Nuban Health Center. The design used in this study analytic survey with cross sectional approach. Total population is 156 toddlers with sample 112 respondents. Statistical test in this study using Chi Square test. Statistical test result with baby weight wih ARI was obtained P-Value of 0,001, which means there is asignificant correlation between baby weight with ARI. Result of statistical tests to the environment with ARI obtained p-value of 0,000 means that there is a significant correlation between the environment habitation of toddler with ARI. Statistical test result immunization status with ARI was obtained p-value of 0,012 means that tere is a correlation immunization status with ARI. In this research, researchers gave advice to the public and health professionals should pay attention to three risk factor of happen ARI for toddler and always gave information and counseling about ways that birth with normal baby weight, a healthy enviroment and a complete immunization status.